Entrepreneurial Competence and Digital Literacy in Enhancing Sales Performance: The Moderating Role of Digital Literacy - Conny Conny (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the influence of entrepreneurial competence on sales performance, the influence of digital literacy on sales performance, and the role of digital literacy as a moderation variable in the relationship between entrepreneurial competence and sales performance. The research uses a quantitative approach with a survey method. Data was collected through a structured questionnaire to 113 sales supervisors at consumer goods distribution companies in the Sulawesi region. Respondents were selected because they had responsibilities in managing the sales team, monitoring sales performance, and utilizing digital-based sales and reporting systems. The measurement was carried out using a five-point Likert scale, while the data analysis used Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS. The results of the study show that digital literacy has a positive but not significant influence on sales performance. These findings show that digital capabilities have not been directly able to improve sales performance. On the other hand, entrepreneurial competence has been shown to have a positive and significant effect on sales performance, which shows that the ability to recognize opportunities, think strategically, and build business relationships plays an important role in improving sales performance. This study also found that digital literacy plays a significant role as a moderation variable in strengthening the relationship between entrepreneurial competence and sales performance. These findings confirm that entrepreneurial competence will result in higher sales performance if supported by an adequate level of digital literacy. This research provides the implication that companies need to develop entrepreneurial competencies and digital capabilities of salespeople simultaneously to improve the effectiveness of sales performance in an increasingly digitized business environment.